PATTERN OF ANTI EPILEPTIC DRUG ADVERSE EFFECT IN TERTIARY REFERRAL HOSPITAL - Damayanti, Ria; Husna, Machlusil; Mondiani, Yeni Quinta; Kurniawan, Shahdevi Nandar (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2020)
Background: Epilepsy is a major chronic neurological problem in the world. The goal of epilepsy therapy is seizure-free and without side effects. The emergence of side effects in patients with epilepsy will be its limitations that can cause the failure of epilepsy therapy. Therefore, it is necessary to do a simple descriptive study, which illustrates the pattern of side effects of anti-epileptic drugs that occur in people with epilepsy, so that later clinicians are more alert and can take preventative measures.Objective: Knowing the pattern of side effects of antiepileptic drugs at the Neurology Outpatient Clinic dr. Saiful Anwar hospital.Methods: This research is an observational descriptive study. Samples were taken by filling the questionnaire at the Neurology Outpatient Clinic dr. Saiful Anwar hospital. Demographic data in this study will be presented in the frequency distribution table. Chi Square test is used to determine the relationship of demographic data, also the pattern of therapy with the side effects that arise.Results: 93 epilepsy patients were involved in the study. More than 40% of patients experience side effects. The most common side effects appear in idiopathic epilepsy (30.1%). Based on the duration of epilepsy, the most side effects appear in epilepsy duration> 10 years (17.2%). However, from the results of the influence test using chi square, there was no significant difference between the duration of epilepsy with the appearance of side effects, even the type of epilepsy (p-value> 0.05). 28 patients who experience side effects, appear after the duration of use of AED 1 - 5 years. It was found that the duration of AED uses affected the emergence of side effects (p-value <0.05).Conclusion: Side effects occur in patients taking anti-epileptic drugs, and are related to the duration of drug use. This data can be used to increase the awareness of clinicians related to the emergence of side effects in patients who consume AED.